Outcomes of Idiopathic Pulmonary Fibrosis Improve with Obesity: A Rural Appalachian Experience. Issue 7 (July 2021) - Sangani, Rahul G.; Ghio, Andrew J.; Mujahid, Hasan; Patel, Zalak; Catherman, Kristen; Wen, Sijin; Parker, John E.
Abstract : Objectives: Obesity can be an independent predictor of fibrosis in tissues, including the liver, heart, and skin. We evaluated a rural Appalachian cohort of idiopathic pulmonary fibrosis (IPF) for its relation to obesity. Methods: Using American Thoracic Society 2018 diagnostic guidelines, an IPF cohort was systematically identified at an Appalachian academic medical center (2015–2019). The cohort was categorized in subgroups of body mass index (BMI) <30 or BMI ≥30 kg/m 2 . Demographics, clinical variables, and treatment details were collected retrospectively and evaluated for their associations with obesity. Results: In our IPF cohort (N = 138), a usual interstitial pneumonia pattern was less prevalent in the obese group (n = 49) relative to the nonobese group (69% vs 85%, respectively). The obese group was younger (mean age 73.27 ± 9.12 vs 77.97 ± 9.59 years) and had a higher prevalence of hypertension (90% vs 72%), hyperlipidemia (83% vs 68%), diabetes mellitus (47% vs 25%), sleep-disordered breathing (47% vs 25%), chronic pain disorders (28% vs 15%), and deep vein thrombosis (19% vs 7%). An increased proportion of obese-IPF patients was seen at a tertiary or an interstitial lung disease center, with more surgical lung biopsies performed and incident diagnosis (ie, within 6 months of presentation) assigned. Only a minority of patients underwent lung transplantation (3.6%), all of them from the obese-IPF subgroup. Approximately 30% of the total IPF cohort died, with a lower mortality observed in the obese group (35% vs 20%, P = 0.017). An increasing BMI predicted a better survival in the total IPF cohort (BMI 25–29.9, 20–24.9, and <20 had mortality rates of 20%, 47%, and 75%, respectively; P < 0.001). Conclusions: Our study represents a first known effort to develop an IPF cohort in a rural Appalachian region. Although they shared an increased burden of comorbidities, the obese subgroup showed less advanced fibrosis with a lower mortality rate relative to nonobese subgroup, suggesting a potential "obesity paradox" in IPF. The study findings significantly advance our understanding of challenges posed by IPF in a rural population that also suffers from an alarming rate of obesity. We highlight the need for the multidisciplinary management of these patients and prospective studies to better define this complex relation. Abstract : Obesity is associated with fibrosis in various tissues, including the liver, heart, kidney, and skin; however, its relation to idiopathic pulmonary fibrosis remains unclear. We systematically identified an idiopathic pulmonary fibrosis cohort at a rural Appalachian academic medical center in accordance with the 2018 American Thoracic Society diagnostic guidelines to describe its association with obesity.